2012
DOI: 10.1111/j.1743-7563.2012.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of health literacy in oncology

Abstract: Health literacy refers to one's ability to obtain, process and understand health information and services to enable sound health decision-making. This is an area of increasing importance due to the complexity of the health system, especially in the cancer setting. A certain level of health literacy is required for patients to fully understand health information and services to make sound decisions about their health care, including decisions about screening and treatment. Previous research has suggested that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 73 publications
5
99
0
3
Order By: Relevance
“…26 Poor health literacy, and poor genetic literacy specifically, is an important problem. 27 In one recent study, 30% of Australians with a university degree had poor health literacy, and the results for Australians without tertiary education were, not surprisingly, worse. 28 Individuals with poor health literacy have more difficulties understanding and remembering health information, 27 and find the complex information surrounding cancer 29 and genetics 30 particularly daunting.…”
Section: Discussionmentioning
confidence: 99%
“…26 Poor health literacy, and poor genetic literacy specifically, is an important problem. 27 In one recent study, 30% of Australians with a university degree had poor health literacy, and the results for Australians without tertiary education were, not surprisingly, worse. 28 Individuals with poor health literacy have more difficulties understanding and remembering health information, 27 and find the complex information surrounding cancer 29 and genetics 30 particularly daunting.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Low health literacy in adults is well known to be associated with misconceptions about a diagnosis and prognosis, which in turn can lead to poor adherence to management plans and greater anxiety levels. [23] However, little is known about how health literacy effects AYA-aged cancer survivors' health outcomes [24] or in fact how they develop health literacy skills at a critical time where they are about to take on from their parents the responsibility for their own healthcare. Whilst AYA aged patients with chronic illness, including AYA-aged cancer survivors dealing with late effects, may demonstrate a desire for a greater degree of autonomy in their healthcare much earlier than compared to their healthy peers, [25] whether they are being equipped with adequate health literacy skills remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is defined as "the capacity to obtain, process and understand health information and services to make health decisions." [14]. Studies have shown that older age and lower education level are strongly associated with lower levels of health literacy [14].…”
Section: Introductionmentioning
confidence: 98%